2011
DOI: 10.17221/136/2010-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Effect of buckwheat flour on microelements and proteins contents in gluten-free bread

Abstract: Krupa-Kozak U., Wronkowska M., Soral-Śmietana M. (2011): Effect of buckwheat flour on microelements and proteins contents in gluten-free bread. Czech J. Food Sci., 29: 103-108.Coeliac disease is an autoimmune gluten-sensitive entheropathy. The only available treatment for it is the life-long adherence to a gluten-free diet although these products are often poor in proteins, minerals, and vitamins. The current study was designed to investigate the effect of buckwheat flour incorporation to a gluten-free experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 23 publications
0
34
2
1
Order By: Relevance
“…A short shelf life, the detection of particles in the mouth during consumption, a dry mouth feeling, and a not really satisfying taste are also some of the disadvantages of gluten‐free bread . Therefore, in recent years numerous studies have focussed on improving the quality of gluten‐free foods, particularly fermented and baked foods, such as bread …”
Section: Definition Of Gluten and Its Technological Importancementioning
confidence: 99%
“…A short shelf life, the detection of particles in the mouth during consumption, a dry mouth feeling, and a not really satisfying taste are also some of the disadvantages of gluten‐free bread . Therefore, in recent years numerous studies have focussed on improving the quality of gluten‐free foods, particularly fermented and baked foods, such as bread …”
Section: Definition Of Gluten and Its Technological Importancementioning
confidence: 99%
“…Ranhotra et al [19] have shown that flour can be fortified to contain Ca at high level without adversely affecting white gluten bread quality. Generally, gluten-free formulas and baked products are poor in minerals, including calcium [20,21]. Calcium fortification of such products could increase the calcium content in the coeliac patients' diet, allowing them to obtain the amount of calcium they need for prophylactic or therapeutic use.…”
Section: Introductionmentioning
confidence: 99%
“…The literature studies showed that the DOI: 10.22616/ERDev2018.17.N393 good chemical composition of buckwheat is retained in backery products, though in pasta it is used mixed with different types of cereals (wheat, millet, rice, etc.) [5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%